The Role of Leading Sector to Reduce Regional Development Inequality in West Papua Province - Michael Albert Baransano; Eka Intan Kumala Putri; Noer Azam Achsani; Lala Kolopaking (Journal of Regional and City Planning, 2016)
The economic development in Indonesia is divided into nine sectors and therefore requires a huge investment. As a result, the government (particularly local government) needs to determine the sectors that are expected to become push factors for other sectors to develop as the prime mover of development in reducing regional disparity. This paper aims to assess the level of developmental disparity between and within the regions of the Province of West Papua from 2005 to 2013, as well as the implementation of the role of the leading sector on the disparity of regional development. The research uses Theil Index, Location Quotient, and Shift Share Analysis approaches and shows that developmental disparity existed as the result of disparity in development regions and is affected by Teluk Wondama, Sorong, Raja Ampat and Fak-Fak regencies. In addition, the result shows that the agricultural sector has the largest influence on the GDP of West Papua over the period of 2005 to 2012. The study also found and recommends that leading sectors in each regency/municipality are an alternative strategy for local government to start development planning, where comparative and competitive advantages of those sectors can play the role of an "engine of growth" in reducing disparities.